Museomics Unveil the Phylogeny and Biogeography of the Neglected Juan Fernandez Archipelago Megalachne and Podophorus Endemic Grasses and Their Connection With Relict Pampean-Ventanian Fescues - Moreno-Aguilar, María Fernanda; Arnelas, Itziar; Sánchez-Rodríguez, Aminael; Viruel, Juan; Catalán, Pilar (Frontiers in Plant Science, 2020)
Oceanic islands constitute natural laboratories to study plant speciation and biogeographic patterns of island endemics. Juan Fernandez is a southern Pacific archipelago consisting of three small oceanic islands located 600-700 km west of the Chilean coastline. Exposed to current cold seasonal oceanic climate, these 5.8-1 Ma old islands harbor a remarkable endemic flora. All known Fernandezian endemic grass species belong to two genera, Megalachne and Podophorus, of uncertain taxonomic adscription. Classical and modern classifications have placed them either in Bromeae (Bromus), Duthieniae, Aveneae/Poeae or Loliinae; however, none of them have clarified their systematic, and evolutionary relationships. Megalachne includes four species, which are endemic to Masatierra (Robinson Crusoe island) (M. berteroniana and M. robinsoniana) and to Masafuera (Alejandro Serkilk island) (M. masafuerana and M. dantonii). The monotypic Podophorus bromoides is a rare endemic species to Masatierra which is only known from its type locality and is currently considered extinct. We have used museomic approaches to uncover the challenging evolutionary history of these endemic grasses and to infer the divergence and dispersal patterns from their ancestors. Genome skimming data were produced from herbarium samples of M. berteroniana and M. masafuerana, and the 163-years old type specimen of P. bromoides, as well as for a collection of 33 species representing the main broad- and fine-leaved Loliinae lineages. Paired-end reads were successfully mapped to plastomes and nuclear ribosomal cistrons of reference Festuca species and used to reconstruct phylogenetic trees. Filtered ITS and trnTLF sequences from these genomes were further combined with our large Loliinae data sets for accurate biogeographic reconstruction. Nuclear and plastome data recovered a strongly supported fine-leaved Fernandezian clade where Podophorus was resolved as sister to Megalachne. Bayesian divergence dating and dispersal-extinction-cladogenesis range evolution analyses estimated the split of the Fernandezian clade from its ancestral southern American Pampas-Ventanian Loliinae lineage in the Miocene-Pliocene transition, followed by long distance dispersal from the continent to the uplifted volcanic palaeo-island of Santa Clara-Masatierra. Consecutive Pliocene-Pleistocene splits and a Masatierra-to-Masafuera dispersal paved the way for in situ speciation of Podophorus and Megalachne taxa.